LCL Filter Design Optimization - Aslanova, Ayna (ADA University, 2025)
Active damping, as implemented in the fourth method, dynamically suppresses resonance and adapts to varying grid conditions, resulting in the lowest THD and highly effective ripple attenuation. Unlike passive damping methods, which rely on fixed resistive elements and incur significant power losses, active damping leverages real-time feedback to enhance efficiency and stability. This makes the fourth method particularly well-suited for addressing the demands of GaN and SiC-based inverter systems, where adaptability and precision are essential. The study demonstrates that this method effectively balances harmonic suppression, energy efficiency, and ease of implementation, making it the most practical solution for next-generation power systems. As renewable energy sources continue to be incorporated into power grids, the role of grid-connected inverter systems becomes ever more critical to maintaining power quality, stability, and adherence to regulatory standards. However, behind the scenes and within these systems itself, LCL filters are vital to suppress harmonics, facilitate efficient energy transfer, and meet demanding performance specifications. On the contrary, the advent of new inverter technologies like gallium nitride (GaN) and silicon carbide (SiC), offers challenges of their own. LCL filter optimization for these converters is in urgent need of creative solutions that deliver reliable performance in the face of changing grid conditions due to the unique switching frequencies and thermal stresses they experience. The thesis investigates for four different approaches on the best optimization stability, low THD and high utilization in LCL filters in three-phase inverter systems. Using a consistent methodology, the study compares harmonic damping, ripple mitigation, component selection, and implementation complexity for each method. The first method is easier but challenges to match up performance with compact component design. The second solves best ripple but does not handle lower-order harmonics well. The third approach finds a sweet spot of performance versus system complexity by making inductance ratios optimal, but mandating elaborate parameter tuning to ensure stability. The fourth method—utilizing active damping through capacitor voltage feedback—demonstrates the highest performance, with great harmonics suppression, dynamic resonance control, and excellent adaptability to the variable grids system. Active damping, as implemented in the fourth method, dynamically suppresses resonance and adapts to varying grid conditions, resulting in the lowest THD and highly effective ripple attenuation. Unlike passive damping methods, which rely on fixed resistive elements and incur significant power losses, active damping leverages real-time feedback to enhance efficiency and stability. This makes the fourth method particularly well-suited for addressing the demands of GaN and SiC-based inverter systems, where adaptability and precision are essential. The study demonstrates that this method effectively balances harmonic suppression, energy efficiency, and ease of implementation, making it the most practical solution for next-generation power systems. This study’s results underline the complex, multi-layered nature of designing LCL filters. It is not sufficient just to size the inductor right; the placement of resonance frequencies and the choice of damping strategies are equally crucial and must also be optimized. This research establishes a clear and comprehensive framework for LCL filter design that is suited to the needs of modern inverter systems, especially next-generation inverters built with GaN and SiC technologies. Combining serious computational with real-world applications, this study strengthens the power electronics field and offers a basis for designing the kind of resilient LCL filters
Keywords: Inverters, Electric -- Design and construction.; Filters (Electricity) -- Design and construction.; Harmonic analysis (Electric engineering).; Renewable energy sources -- Integration.; LCL filters.; Power quality.